Why do people die in earthquakes? the costs, benefits and institutions of disaster risk reduction in developing countries - Kenny, Charles (Policy research working paper, 2009)
"Every year, around 60,000 people die worldwide in natural disasters. The majority of the deaths are caused by building collapse in earthquakes, and the great majority occurs in the developing world. This is despite the fact that engineering solutions exist that can almost completely eliminate the risk of such deaths. Why is this? The engineering solutions are both expensive and technically demanding, so that the benefit-cost ratio of such solutions is often unfavorable compared with other interventions designed to save lives in developing countries. Nonetheless, a range of public disaster risk-reduction interventions (including construction activities) are highly cost effective. The fact that such interventions often remain unimplemented or ineffectively executed points to a role for issues of political economy. Building regulations in developing countries appear to have limited impact in many cases, perhaps because of limited capacity and the impact of corruption. Public construction is often of low quality - perhaps for similar reasons. This suggests approaches that emphasize simple and limited disaster risk regulation covering only the most at-risk structures and that (preferably) can be monitored by non-experts. It also suggests a range of transparency and oversight mechanisms for public construction projects. "--World Bank web site